Strategi Peningkatan Daya Saing UMKM di Kabupaten Sinjai melalui Optimalisasi Digital Marketing - Aam Azatil Isma; Sari Astriani R; Sri Aisyah Yope (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze strategies for increasing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) through optimizing digital marketing in Sinjai Regency. In the era of digital transformation, technological adaptability is a key determinant of MSMEs' survival in the face of increasingly competitive markets. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation of MSMEs actively using digital platforms. The research findings indicate that although MSMEs have begun utilizing social media platforms such as Instagram, Facebook, and WhatsApp, their effectiveness is still hampered by low digital literacy, limited technological infrastructure, and a lack of consistency in content management. Optimization strategies identified include strengthening digital branding identity, systematic target market mapping, improving visual content quality, and measurable use of paid advertising. The analysis shows that optimal use of digital marketing strategies significantly impacts market reach expansion beyond the region and a gradual increase in sales volume. This study recommends the need for synergy between the local government and stakeholders in providing technical training and ongoing mentoring to build an inclusive digital ecosystem for MSMEs in Sinjai Regency.